The phenomenon of income smoothing in banking companies listed on the Indonesian stock exchange and the factors that influence it - Apiek Anggereni Surya Kusuma (Institute of Accounting Research and Novation (IARN), 2021)
The objective of this research are to prove empirically regarding income smoothing practice in banking companies in Indonesia Stock Exchange and to identify some factors which are suspected have an influence on income smoothing practice, such as company size, debt to equity, and profitability. This research involved 14 listed banking companies in Indonesia Stock Exchange during 5 years from 2003 until 2007. The Eckel Index was used to classify samples between smoothing company and non smoothing company. The statistical method which used in univariate test were Independent Sample T-Test and Mann-Whitney U Test, while for the multivariate test Binary Logistic Regression (Logit) was used. The researcher used statistical software SPSS version 16 to process both of the test. The result using Eckel Index showed that there are 9 banking companies from 14 samples practiced income smoothing. The result of univariate test indicated that company size, debt to equity, and profitability did not prove to have significant difference between smoothing company and non smoothing company. The result of multivariate test also indicated that company size, debt to equity, and profitability did not prove to have an influence on income smoothing practice.